The effect of Arabic language and literature on the novel "Ibn al-Waqt" by Nazir Ahmad al-Dahlawi - Dr. Abua Bakar; Dr. Sabahat Afzal (jihat-ul-islam, 2021)
The Urdu language and literature has been influenced by the Arabic language to a large extent in terms of vocabulary, structures, calligraphy and phonology. Urdu writers and poets are impressed by the Arabic language and literature as they use quotations from the Holy Qur’an, the Saying of the Prophet, Arabic poetry and proverbs. Although the Urdu fiction and the novel in the first phase had direct contact with English literature and was influenced by the West, but the character of the Arabic and Persian language prevailed in its style, texture, form and even in its environment. The Urdu novelist quotes from the Qur’anic text in particular and from Arabic literature and Islamic history in general, as we find dozens of examples among Urdu novelists such as Deputy Nazeer Ahmad, Abdul Haleem Sharar and Rashid ul Khairi. This research paper deals with the effect of Arabic language and literature on the novel “Ibn ul Waqt” of Nazeer Ahmad. After brief sketch of his life and literary work and short introduction of his novel "Ibn al-Waqt", its plot, style and characters, the various aspects of influence of Arabic language and literature on the novel has been described.